Students’ food consumption in a school canteen : analysis of what they choose from the canteen gallery and what they discard, by gender and age - Carvalho, Graça Simões de (2013)
Recently, many countries, including Portugal, have implemented strategies for promoting young people’s healthy lifestyles, and school canteens are seen as appropriate places to encourage healthy eating (Aracenta-Bartrina et al., 2008). In addition to educate and empower students to make healthy choices, canteens are also seen as socialization spaces where the pleasure for healthy meals must also be promoted (Atie-Guidalli, 2012). This work intended to evaluate not only the quality of the canteen food provided in a school (in the Southern region of Portugal, Alentejo) but also the students’ food choices and opinions about the canteen service, in order to assess the efficiency of the national canteen programme in this school. The aim was to find evidences of good practices as well as needs for improvement. Therefore, the objectives of this study were (i) to characterise the school canteen conditions, both the food service provided and the students’ perceptions about it; (ii) to observe the students’ food choices and preferences; (iii) to analyse students’ food consumption, i.e. what they actually eat from the complete meal and what they discard; (iv) to find significant statistic differences between gender and between school level groups; (v) and, if pertinent, to formulate recommendations to improve the canteen service and the students’ healthier behaviour.